2007
DOI: 10.1128/iai.00052-07
|View full text |Cite
|
Sign up to set email alerts
|

Role of Motility and the flhDC Operon in Escherichia coli MG1655 Colonization of the Mouse Intestine

Abstract: Previously, we reported that the mouse intestine selected mutants of Escherichia coli MG1655 that have improved colonizing ability (M. P. Leatham et al., Infect. Immun. 73:8039-8049, 2005). These mutants grew 10 to 20% faster than their parent in mouse cecal mucus in vitro and 15 to 30% faster on several sugars found in the mouse intestine. The mutants were nonmotile and had deletions of various lengths beginning immediately downstream of an IS1 element located within the regulatory region of the flhDC operon,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
98
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(106 citation statements)
references
References 42 publications
8
98
0
Order By: Relevance
“…The specific growth rate of the cells with IS5 in flhD was slightly lower, and the cells had a lower yield (6 ± 1% reduction) (Figure 2c). This result is consistent with an earlier study, which shows that MG1655 (IS1 inserted upstream of flhDC) grew more slowly than MG1655 that lacks IS1 upstream of flhDC due to the reduction in energy available for growth due to the enhanced motility (Gauger et al, 2007). For our work, when IS5 was cured from the upstream region of flhD þ , growth, motility and biofilm formation were restored to the wild-type values (Figure 2), which demonstrates that the increase in motility, the increase in early biofilm formation, and the decrease in growth are due to the presence of IS5 in promoter of flhDC.…”
Section: Is5 Insertion Upstream Of Flhd þ Increases Motility and Biofsupporting
confidence: 93%
See 2 more Smart Citations
“…The specific growth rate of the cells with IS5 in flhD was slightly lower, and the cells had a lower yield (6 ± 1% reduction) (Figure 2c). This result is consistent with an earlier study, which shows that MG1655 (IS1 inserted upstream of flhDC) grew more slowly than MG1655 that lacks IS1 upstream of flhDC due to the reduction in energy available for growth due to the enhanced motility (Gauger et al, 2007). For our work, when IS5 was cured from the upstream region of flhD þ , growth, motility and biofilm formation were restored to the wild-type values (Figure 2), which demonstrates that the increase in motility, the increase in early biofilm formation, and the decrease in growth are due to the presence of IS5 in promoter of flhDC.…”
Section: Is5 Insertion Upstream Of Flhd þ Increases Motility and Biofsupporting
confidence: 93%
“…This occurrence of a motile sub-population of cells was also reported for MG1655 fnr from an inoculum of poorly motile MG1655 fnr on soft-agar plates, and PCR screening confirmed that IS5 inserted into the flhDC regulatory region in the same manner (Barker et al, 2004). The sequenced K12 strain, MG1655, is a relative of BW25113 (Baba et al, 2006), and is highly motile because of a similar IS1 insertion sequence upstream of flhD þ (Blattner et al, 1997;Gauger et al, 2007).…”
Section: Is5 Hops Upstream Of Flhd þ Only When Cells Swim On Motilitysupporting
confidence: 72%
See 1 more Smart Citation
“…Motility is a major trait involved in both the pathogen and commensal lifestyles of E. coli (16,34). Different orthologous genes present on several PAIs of E. coli 536 were shown to be involved in the regulation of motility in other ExPEC strains (57,58).…”
Section: Resultsmentioning
confidence: 99%
“…We discuss how such observed speed increases can lead to negative taxis previously reported. Our study emphasizes the importance of investigating bacterial motility in environments that mimic natural habitats, in the effort to understand the role and evolutionary advantage swimming offers to bacterial cells [Lackraj et al, 2016, Gauger et al, 2007, Tamar et al, 2016.…”
Section: Origins Of Osmokinesismentioning
confidence: 89%